Explore the pharmacological basis of ShengJiYiSui decoction in the treatment of amyotrophic lateral sclerosis based on network pharmacology and molecular docking technology: ShengJiYiSui decoction in the treatment of ALS - Luo, Song; Yang, Lijuan; Ma, Bo; Wang, Xiaorui; Lu, Yi; Ma, Shouliang; Wang, Dan; Qu, Hongdang; Zou, Liangyu (Cellular and Molecular Biology, 2023)
Neurodegenerative illnesses have long been handled clinically by traditional Chinese medicine. This study is the first time to explore the pharmacological basis of application in amyotrophic lateral sclerosis (ALS) through network pharmacology and molecular docking techniques. In the present investigation, the TCMSP database and HIT2 database were examined for 9 TCM constituents of Sheng Ji Yu Sui Decoction (SJYSD), and the desired sites for the components were searched in the Drugbank database. and the Sjysd-target network was constructed. Associated targets for Amyotrophic lateral sclerosis (ALS) were then retrieved and collected in the OMIM, TTD, Genecards and DisGeNET databases. Protein-protein interaction and enrichment analysis were performed for the common targets of drugs and diseases, and molecular anchoring for the chosen core targets and related molecules was carried out. The results showed that SJYSD had 100 active compounds corresponding to 598 targets. ALS has a total of 5,325 genes. SJYSD and ALS share 163 genes, and these targets involve PI3K-AKT signaling, p53 signaling and IL-17 signaling, etc. The core components of luteolin and quercetin were discovered and may be used to treat ALS by regulating PI3K-AKT signaling pathway by HSP90AB1 protein.